Perkembangan kota banda Aceh pasca bencana tsunami 2004 - Raja Al-Fath; Agam Marsoyo (Universitas Gadjah Mada, 2023)
Every city keeps growing as a result of population growth and has an impact on space requirements. Same as Banda Aceh City which continues to grow, but its development has stopped due to the 2004 tsunami disaster. Residential areas tend towards the north or the coast, which is tsunami-prone zone. The purpose of this study is to describe the direction and built-up area development of Banda Aceh City after the tsunami from 2005-2011, 2011-2015, and 2015-2020. The data used in this study is spatial data such as maps and satellite images sourced from Banda Aceh planning and development agency. Data analysis uses spatial approach with the overlay method. Development of the built-up area of Banda Aceh city based on the period 2005-2011, 2011-2015, and 2015-2020 shows that the built-up area leads to the northern and southern parts of Banda Aceh City. Development of the northern part of the city, Districts of Jaya Baru, Meuraksa, Kuta Raja, Kuta Alam, and Syiah Kuala was a result of the rehabilitation and reconstruction efforts such as housing, roads, and facilities after tsunami and turned the ponds and vacant land into housing and service trading areas. The northern part of Banda Aceh City was tsunami hazard-prone zone. Meanwhile, development of the southern part of the city, districts of Banda Raya, Lueng Bata, and Ulee Kareng, was influenced by Mohamad Hasan and Ali Hasyimi street which triggered the development of residential areas, office areas, service trading areas, and public facilities. Southern part of the city was not directly affected by the tsunami disaster. In addition, built-up area development has spread to the Aceh Besar regency.